The Role of Women in The “Life After the Pandemic” of Pope Francis - Cuizon, Melchor Labao (Indonesian Center for Religion and Society Studies (InTReSt), 2024)
This article focuses on Pope Francis Urbi et orbi (from the city of Rome to the entire world) a papal address that invites humanity to listen to the silent and invisible voices of the field who contributed much to the fight against COVID-19 yet suffered discrimination and inequality. Highlighted in the text were the voices of the field, the vulnerable humanity severely affected by the pandemic yet their works and contributions were made hidden and invisible. These are women behind the pandemic whose dedication as essential workers is unquestionable yet poorly recognized in a male-dominated society. In anticipation of the tragic event that proceeds after the pandemic, the Pope invites everyone to pray and reflect on procuring the grace of God as a fundamental instrument of redirecting one's undesirable attitude toward women an essential key toward integral human development and the rebuilding of humanity in the spirit of solidarity. Thus, the paper exposes the role of women during the pandemic, and (2) argues that gender sensitivity is possible through prayer and reflection as articulated by the Pope.